Hubungan antara pengetahuan gizi, body image, tingkat stres, dan Korean wave terhadap pola makan sehat siswi SMA Negeri 1 Jakarta - Audrey Aurelia; Laras Sitoayu; Idrus Jus'at (UHAMKA PRESS, 2026)
The problem of overweight and obesity among adolescents is increasing globally, including in Indonesia, and one of the contributing factors is diet. Healthy eating habits are influenced by various internal and external factors, including nutritional knowledge, body image perceptions, stress levels, and exposure to the Korean wave. Korean wave refers to the influence of Korean popular culture, which includes food trends, eating habits, beauty standards, and lifestyles spread through mass media and social media, which have the potential to influence food preferences, eating behaviors, and adolescents' perceptions of healthy eating patterns. This study aimed to examine the relationships among nutritional knowledge, body image, stress levels, the Korean wave, and healthy eating patterns among female students at SMA Negeri 1 Jakarta using a quantitative cross-sectional design. The sample size for this study was determined using G-Power software, resulting in 51 female students as subjects. Data were collected through questionnaires and analyzed using Pearson's correlation test. The results showed significant relationships between nutritional knowledge (p=0.042; r=0.287), body image (p=0.021; r=0.323), stress levels (p=0.002; r=0.421), and healthy eating patterns. Meanwhile, the Korean Wave showed no significant relationship (p=0.149; r=0.205). The three variables, namely nutritional knowledge, body image, and stress levels, were related to healthy eating patterns, with stress levels having the strongest correlation. These findings emphasize the importance of a multidimensional approach to shape healthy eating behaviors among adolescent girls.